2020
DOI: 10.1108/sajbs-01-2020-0010
|View full text |Cite
|
Sign up to set email alerts
|

The nexus of economic growth, priority sector lending and non-performing assets: case of Indian banking sector

Abstract: PurposeIn recent years, the Indian banking sector is facing a major cause of concern in the form of Nonperforming Assets (NPA), and the priority sector lending (PSL) is generally recognized as the major factor contributing to it. Thus, the present study has been carried out with the objective of examining the relationship between priority sector lending and GDP growth. Thereafter, the role of PSL and certain other bank-specific, indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 60 publications
0
11
0
Order By: Relevance
“…Their findings show that unemployment and the exchange rate are the main determinants of NPLs. Gaur and Mohapatra (2020) and Mishra et al (2021) study the nexus between NPLs and macroeconomic variables in the Indian banking system. Both papers document policymakers' importance of monitoring macroeconomic conditions to ensure a more robust Indian financial system.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Their findings show that unemployment and the exchange rate are the main determinants of NPLs. Gaur and Mohapatra (2020) and Mishra et al (2021) study the nexus between NPLs and macroeconomic variables in the Indian banking system. Both papers document policymakers' importance of monitoring macroeconomic conditions to ensure a more robust Indian financial system.…”
Section: Literature Overviewmentioning
confidence: 99%
“…First, to our knowledge, it is the first work that studies the impact of the macroeconomic environment in Italy during the recent period. Several papers have analyzed this relationship in the U.S. (Ghosh 2015), European (Makri et al 2014;Rinaldi and Sanchis-Arellano 2006), Greek (Anastasiou et al 2019;Konstantakis et al 2016;Louzis et al 2012), France and Germany (Chaibi and Ftiti 2015), India (Gaur and Mohapatra 2020;Mishra et al 2021), and other world regions (Beck et al 2015;Espinoza and Prasad 2010;Hada et al 2020;Kjosevski et al 2019;Nkusu 2011;Tanasković and Jandrić 2015;Zheng et al 2020;Žunić et al 2021) contexts. However, only Bofondi and Ropele (2011) studied the relationship between macroeconomic variables and bad loans in the Italian context from 1990 to 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Biekpe (2011) argued that larger banks face lower of loans issue since they have the likelihood of achieving well-diversified loan portfolios. However, Gaur and Mohapatra (2021) did not find any significance of bank size on NPLs. Therefore, this paper assumes-H 5 There is a significant nonlinear impact of size on NPLs.…”
Section: Bank Size and Nplsmentioning
confidence: 64%
“…From the analysis of the academic literature, it can be concluded that various studies and papers have examined the impact of NPLs on bank lending (Salas and Saurina 2002;Espinoza and Prasad 2010;Bofondi and Ropele 2011;Louzis, Vouldis, and Vasilios 2012;Abid, Nejib-Ouertani, and Zouari-Ghorbel 2014;Bijsterbosch and Falagiarda 2015;Kjosevski, Petkovski, and Naumovska 2019;Gaur and Mohapatra 2020) and economic activity (Baboučak and Jančar 2005;Saurina and Jimenez 2006;Rinaldi and Sanchis-Arellano 2006;Kauko 2012;Klein 2013;Škarica 2014;Beck, Jakubik, and Piloiu 2015;Khan, Siddique, and Sarwar 2020;Kucuk, Ozlu, and Yunculer, 2021). The gap in the literature is that there are not so many papers investigating the linkage between NPLs and fiscal policy (Nurja and Kufo 2016;Dimitrios, Louri, and Tsionas 2016), so this gap was covered.…”
Section: Related Literature Reviewmentioning
confidence: 99%